2022
DOI: 10.1111/ijfs.16104
|View full text |Cite
|
Sign up to set email alerts
|

Fish processing waste: a novel source of non‐conventional functional proteins

Abstract: Fish waste has now become one of the serious problems worldwide, and its disposal without proper management could result in serious environmental pollution and nutrient loss. These wastes contain several biological and nutritional compounds, if recovered has a lot of promise. With the recent technological developments, many bioactive and functional compounds can be recovered from these wastes. The vast quantity of bioactive chemicals found in seafood processing by-products has prompted the development of valor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…Fish contain nutraceuticals like PUFAs, peptides, vitamins and minerals. Fish frames provide easily digestible muscle proteins (Rana et al ., 2023). Fish oil extraction offers value‐added human food supplements (Debbarma et al ., 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Fish contain nutraceuticals like PUFAs, peptides, vitamins and minerals. Fish frames provide easily digestible muscle proteins (Rana et al ., 2023). Fish oil extraction offers value‐added human food supplements (Debbarma et al ., 2023).…”
Section: Introductionmentioning
confidence: 99%
“…According to the Food and Agriculture Organization (FAO), fish production has been growing at a 3% yearly rate since 1961, reaching 214 million tons of fish produced in 2020 [ 1 , 2 ]. The amount of fish waste produced in recent years has therefore increased noticeably and it is believed that almost two-thirds of that is discarded, raising serious economic and environmental issues [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the food business is always coming up with novel strategies to cut production costs, boost earnings, and enhance the nutritional value of its goods (Monteiro et al ., 2016). Therefore, many studies reported the production of pasta with the fortification of different sources of protein isolates, such as dairy, marine, and grains (Raina et al ., 2023; Rana et al ., 2023). The protein isolates generally employ >90% protein and the quality of the protein depends upon the source.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the eating habit of junk food may cause serious sufferings from many diseases such as cardiovascular diseases, mental health issues, obesity, marasmus, and kwashiorkor. Thus, consumers are looking for products with high nutrition in a cost‐effective manner without impairing their regular taste (Surasani et al ., 2019; Singh et al ., 2021; Rana et al ., 2023). To meet these demands of consumers, the incorporation of low‐cost fish can be an effective approach.…”
Section: Introductionmentioning
confidence: 99%